Perinatal Grief Among Poor Rural and Urban Women in Central India - Roberts LR; Renati SJ; Solomon S; Montgomery S (Dove Medical Press, 2021)
Lisa R Roberts,1 Solomon J Renati,2 Shreeletha Solomon,3 Susanne Montgomery4 1School of Nursing, Loma Linda University, Loma Linda, CA, 92350, USA; 2Psychology Department, Veer Wajekar A. S. & C. College, University of Mumbai, Navi Mumbai, 400702, India; 3Martin Luther Christian University, Shillong, Meghalaya, 793006, India; 4School of Behavioral Health, Director of Research, Behavioral Health Institute, Loma Linda University, Loma Linda, CA, 92350, USACorrespondence: Lisa R RobertsLoma Linda University School of Nursing, 11262 Campus Street, Loma Linda, CA, 92350, USAEmail lroberts@llu.eduPurpose: Given the pressures surrounding women’s reproductive role in India, and persistent high rates of perinatal death, the purpose of this study is to describe and compare poor rural and urban Indian women’s experiences of perinatal grief.Participants and Methods: Two cross-sectional studies were compared on shared quantitative variables. Poor rural (N = 217) and urban, slum-dwelling (N = 149) Central Indian women with a history of stillbirth, and/or infant death were recruited with the aid of local community health workers. Trained, local, gender, and linguistically matched research assistants conducted the structured interviews. Shared quantitative variables include demographics, Social Provision Scale, Shortened Ways of Coping-Revised, Perinatal Grief Scale, social norms and autonomy.Results: While similar with respect to SES, age, number of living sons and perinatal loss experiences, these samples of poor women differed significantly across many variables, most notably women’s household position, joint family living, number of live daughters, religious coping, autonomy, and degrees of perinatal grief. While perinatal grief was significantly associated with many variables bi-variably, most lost their relative influence in our stepwise multivariable modeling within site (rural/urban), with only social norms and social support remaining significant for rural (31% of variance) and wishful thinking and social norms for urban participants (38.4% of variance). In the combined sample household position, social support and social norms remained significant and explained 53.6% of the adjusted variance.Conclusion: In both samples, perinatal grief was high following perinatal loss. Both groups of women with perinatal loss have increased risk of mental health sequelae. Notably, the context affected how they experienced perinatal grief, with rural women’s grief being higher and more affected by their societal pressures and isolation. Such nuances are important considerations for much-needed tailored approaches to future interventions.Keywords: stillbirth, infant death, bereavement, maternal, mental health risk